SAT0408 Long Term Outcome of Primary Antiphospholipid Syndrome Patients: A Multicenter Study. (9th June 2015) - Taraborelli, M.; Dall'Ara, F.; Reggia, R.; Fredi, M.; Gerosa, M.; Massaro, L.; Tonello, M.; Cacoub, P.; Costedoat-Chalumeau, N.; Franceschini, F.; Meroni, P.L.; Piette, J.C.; et al.
Abstract : Background: Data on the long-term outcome in primary antiphospholipid syndrome (PAPS) patients (pt) are still very limited. Objectives: To assess the prevalence of recurrences, organ damage, severe comorbidities (infections, hemorrhages, cancers), mortality, evolution in connective tissue disease (CTD), in long-standing PAPS.To compare non criteria manifestations, serological alterations, cardiovascular risk factors and therapy between onset and follow-up. Methods: Medical records of PAPS pt followed in 6 centers for ≥15 years were retrospectively reviewed.Chi square for categorical and Student t test for continuous variables were used.P<0.05 was considered significant. Results: One hundred and sixteen pt (88% females) with PAPS followed between 1983 and 2014 with mean age at diagnosis of 33 (±10) and mean follow-up of 19 years (±5) were studied.Fifty-one pt (44%) had at least a thrombotic event during follow-up. Thromboses were more frequent in patients with previous thrombotic history (p:0.003, OR:4.68, 95%CI:1.6-14.3) and anticoagulant treatment was not protective against recurrences (p:not significant).Six pt (5%) had a catastrophic event. Fifty-two women had 87 pregnancies, that were successful in 76% of cases. Thirty-one (27%) pt had organ damage (permanent loss of function) in at least one system (15% neurological, 3% renal, 5% cardiac, 4% ocular, 1% peripheral vascular, 1% osteoarticular, 1% gastrointestinal).Damage was significantly associated to a thrombotic history (p:0.008, OR:11.8, 95%CI:1.6-245.3) and to arterial events (p<0.001, OR:17.1, 95%CI:4.4-77.4), but not to any demographical, serological or therapeutical variable. An anatomical damage (documented ischemic lesion) was present in 54% of pt (n=63).Twenty-four major bleeding episodes were recorded in 18 pt all on anticoagulants.Severe infections (4 bacterial, 2 viral) affected 6 pt (5%).A cancer (solid in 100%) was diagnosed in 8 pt (7%) at a mean age of 51 years (±6).One patient (1%) with a chronic bowel ischemia died for sepsis.Fourteen pt (12%) developed a CTD (7 Systemic Lupus Erythematosus, 2 Sjogren, 5 Undifferentiated CTD).Compared to diagnosis at the end of the follow up we observed: less patients with anti-cardiolipin IgG (p:0.014) but more with antinuclear antibodies (p:0.01) and C4 reduction (p:0.025);less using estroprogestinics (p<0.001), more with hypercholesterolemia (p 0.043), hypertension (p:0.004), cancer (p:0.02);more using steroids (p:0.04), hydroxychloroquine (p<0.001), immunosuppressants (p<0.01), anticoagulants (p:0.003), anti-hypertensive drugs (p<0.001). Conclusions: Despite therapy, a high proportion of pt experienced new thrombotic events, while pregnancy outcome was significantly improved.Organ damage developed in a significant proportion of pt and was associated with arterial events. Evolution in CTD was not common but occurred during follow-up.PAPS is a disease of young people characterized by relevant morbidity and premature mortality. Disclosure of Interest: None declared